A history of the world in 10 1/2 chapters - Barnes, Julian (Pan Books Ltd, in association with Jonathan Cape Ltd, 1990)
This is, in short, a complete, unsettling, and frequently exhilarating vision of the world, starting with the voyage of Noah's ark and ending with a sneak preview of heaven!